TEMPERATURA DE SUPERFICIE EN EL VALLE DEL RÍO NEUQUÉN UTILIZANDO IMÁGENES LANDSAT - Marisa G. Cogliati (Boletín Geográfico)
Studies of surface and air temperature from LANDSAT need a great density of meteorological stations following the altitudinal variation and complexity of terrain. Alternative methods for the study of the spatial distribution are useful. In this paper, the seasonal variation of surface temperature is analyzed by LANDSAT7 ETM + thermal channel information considering an area of the productive valley of the Neuquén River. Landsat 7 ETM + images offer information with 60 m of spatial resolution; its behavior showed agreement with topography. The calculation of surface temperature using LANDSAT imagery should include surface meteorological data: atmospheric water vapor content and mean air temperature near to the surface, simultaneously to the passage of the satellite. The data were corrected using Atmospheric Correction Parameter Calculator, available online. Areas near Neuquén river show lower surface temperature in summer, while the southeastern areas presented surface temperature between 4ºC and 5°C smaller, and the zones of greater slope in the northern area on the plateau presented surface temperature approximately 4°C. In summer, the cultivated area can be more clearly differentiated, that would be indicative of phenological changes of fruit trees and the greater contrasts of temperature due to the differential warming from various surfaces. Temperature differences were smaller in winter. In winter, the temperature of surface of the humid areas, zones with water and zone of the plateau is relatively greater to the surrounding areas.